Prediksi Kebangkrutan Terhadap Harga Saham Dengan Model Altman Z-Score, Zmijewski Dan G-Score - Risma Dwi Nurminawati (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
The purpose of this study was to determine the effect of Altman Z-score, Zmijewski, Gscore on stock prices. The samples used in this study were propertyand real estate companies listed on the Indonesia Stock Exchange for the 2015-2019 period with a sample of 35 companies obtained using purposive sampling. The analysis used is multiple linear regression and classical assumption test. The results show that the Altman Z-score model has a significant effect on stock prices with a significant value of 0,000. Zmijewski model has a significant effect on stock prices with a significant value of 0,005. The G-score model also has a significant effect on stock prices with a significant value of 0,000. There is a simultaneous influence between independent variables namely Altman Z-score, Zmijewski dan G-score with the dependent variable namely Stock Prices